Déficit de la lectura en proceso formativo de educación básica media - Muso Avilés, Kléber Fabián (2017)
The project entitled "DEFICIT OF READING IN THE BASIC EDUCATION TRAINING PROCESS" focuses on the problems that today are presented in children with low reasoning, reading comprehension and text production. The objective of this research, is to diagnose the importance of the processes, levels, disorders among other contents that intervene in reading. The Educational Unit "Juan Abel Echeverría", presents a high percentage of students who don´t reach an optimal level of learning, nor base adequate reading habits, becoming a problem in the teaching-learning process; at the same time, there are teachers who don´t want to update the methodology and strategies because there is no opening to improve their skills or the contents of the Curricular Updating and Strengthening are unknown, which is why students present a traditional education without reaching the goals with performance criteria of the language and literature area. For this research project objectives are set to develop that benefit the institution with the intention of knowing the factors of the reading deficit, in addition, investigate the theorical foundaments that allow knowing the subject from a scientific perspective, as well as diagnose methodological processes that collaborate with the solution of this problem. In this way, research instruments were applied to the educational community, in order to collect truthful information. The methodology applied is formative research to know the causes and consequences that influence reading. This research favors the teaching and learning process because it was analyzed why there is a lot of difficulty when reading or understanding a text, for this reason, it will invite teachers and students to know the innovative strategies that should be used, so that help to develop their reading ability, guaranteeing a correct learning in order that students can have a meaningful learning and stand out in the place they are, and make reading a good habit.